Biosynthesis and emission of methyl hexanoate, the major constituent of floral scent of a night-blooming water lily Victoriacruziana. (November 2021) - Jiang, Yifan; Liu, Guanhua; Zhang, Wanbo; Zhang, Chi; Chen, Xinlu; Chen, Yuchu; Yu, Cuiwei; Yu, Dongbei; Fu, Jianyu; Chen, Feng
Abstract: Among the factors that have made flowering plants the most species-rich lineage of land plants is the interaction between flower and insect pollinators, for which floral scent plays a pivotal role. Water lilies belong to the ANA (Amborellales, Nymphaeales, and Austrobaileyales) grade of basal flowering plants. In this study, Victoria cruziana was investigated as a model night-blooming water lily for floral scent biosynthesis. Four volatile compounds, including three benzenoids and one fatty acid methyl ester methyl hexanoate, were detected from the flowers of V. cruziana during their first bloom, with methyl hexanoate accounting for 45 % of total floral volatile emission. Emission rates were largely constant before significant drop starting at the end of second bloom. To understand the molecular basis of floral scent biosynthesis in V. cruziana, particularly methyl hexanoate, a transcriptome from the whole flowers at the full-bloom stage was created and analyzed. Methyl hexanoate was hypothesized to be biosynthesized by SABATH methyltransferases. From the transcriptome, three full-length SABATH genes designated VcSABATH1 - 3 were identified. A full-length cDNA for each of the three VcSABATH genes was expressed in Escherichia coli to produce recombinant proteins. When tested in in vitro methyltransferase enzyme assays with different fatty acids, both VcSABATH1 and VcSABATH3 exhibited highest levels of activity with hexanoic acid to produce methyl hexanoate, with the specific activity of VcSABATH1 being about 15 % of that for VcSABATH3. VcSABATH1 and VcSABATH3 showed the highest levels of expression in stamen and pistil, respectively. In phylogenetic analysis, three VcSABATH genes clustered with other water lily SABATH methyltransferase genes including the one known for making other fatty acid methyl esters, implying both a common evolutionary origin and functional divergence. Fatty acid methyl esters are not frequent constituents of floral scents of mesangiosperms, pointing to the importance for the evolution of novel fatty acid methyltransferase for making fatty acid methyl esters in the pollination biology of water lilies. Graphical abstract: Image 1 Highlights: Methyl hexanoate is a major constituent of floral scent of Victoria cruziana. SABATH methyltransferases were identified as key enzymes for its biosynthesis. Methyl hexanoate biosynthesis was inferred to have evolved multiple times.